Click and mortar of retail banking : a case study in Hong Kong. - Ching, Keng Jin. (2008)
This report explores how banks in Hong Kong have changed their ways in the conduct of retail banking businesses with the implementation of Internet banking, and how these changes have affected the bricks-and-mortar distribution channels of banks.